The impact of social media on the development of international relations in Western Balkan countries - Daku, Selim (Array, 2018)
Nowadays, the use of social media has grown worldwide, and this has resulted in increased influence on international relations. Other researches show that this form of communication is increasing, so the research goal is to determine the extent of social media impact on the development of international relations in the Western Balkan Countries. To achieve the results, it was conducted an online survey with experts and representatives of institutions, and through the questionnaire was evaluated the use of social networks, the effects of use, transparency and reliability. The collected data were analyzed carefully, and came to the conclusion that; respondents highly assess the impact of social media on international relations development in Western Balkan countries. The social media have achieved higher effect, also without the influence of international policy leaders, in some areas such as transparency.